A Smartphone App Designed to Empower Patients to Contribute Toward Safer Surgical Care: Community-Based Evaluation Using a Participatory Approach - Russ, Stephanie; Latif, Zahira; Hazell, Ahmarah Leah; Ogunmuyiwa, Helen; Tapper, Josephine; Wachuku-King, Sylvia; Sevdalis, Nick; Ocloo, Josephine (JMIR Publications, 2020)
BackgroundMySurgery is a smartphone app designed to increase patient and carer involvement in behaviors that contribute toward safety in surgical care. ObjectiveThis study presents a pilot evaluation of MySurgery in which we evaluated surgical patients' perceptions of the app in terms of its content, usability, and potential impacts on communication and safety. MethodsA participatory action research (PAR) approach was used to formulate a research steering group consisting of 5 public representatives and 4 researchers with equal decision-making input. Surgical patients were recruited from the community using multiple approaches, including Web based (eg, social media, recruitment websites, and charitable or voluntary organizations) and face to face (via community centers). Participants referred to MySurgery before, during, and after their surgery and provided feedback via an embedded questionnaire and using reflective notes. ResultsA diverse mix of 42 patients took part with good representation from 2 "seldom heard" groups: those with a disability and those from a black, Asian, or minority ethnic group. Most were very supportive of MySurgery, particularly those with previous experience of surgery and those who felt comfortable to be involved in conversations and decisions around their care. The app showed particular potential to empower patients to become involved in their care conversations and safety-related behaviors. Perceptions did not differ according to age, ethnicity, or length of hospital stay. Suggestions for improving the app included how to make it more accessible to certain groups, for example, those with a disability. ConclusionsMySurgery is a novel technology-driven approach for empowering patients to play a role in improving surgical safety that seems feasible for use within the United Kingdom's National Health Service. Adopting a PAR approach and the use of a diversity strategy considerably enhanced the research process in terms of gaining diverse participant recruitment and patient and public involvement. Further testing with stakeholder groups will follow.